PERLINDUNGAN HAK CIPTA SINEMATOGRAFI FILM YANG DISEBARLUASKAN MELALUI APLIKASI TELEGRAM SELAMA COVID-19: COPYRIGHT PROTECTION OF FILM CINEMATOGRAPHIES DISSEMINATED VIA THE TELEGRAM APPLICATION DURING COVID-19 - Inge Dwisvimiar; Rully Syahrul Mucharom; Isdal Alzafar (Journal Presumption of Law, 2024)
People during the Covid-19 period switched to watching movies from movie theaters to digital by paying application service fees, but not all people want to pay a fee to watch and switch to watching movies through the Telegram application, the movies in the Telegram application are pirated movies. The purpose of the research is: to analyze the protection of cinematographic copyright of films disseminated through the Telegram application during the Covid-19 pandemic and to explain, legal settlements in cases of violation of cinematographic copyright of films disseminated through the Telegram application during the Covid-19 pandemic. The research method used is the Normative-Empirical method. The data sources used are secondary data sources primary data sources. Data collection techniques are literature study and interviews.  Data analysis used qualitative data analysis. The result of this study is that, the legal protection of cinematographic films disseminated through the Telegram application during the Covid-19 pandemic is through the closure of accounts or content based on recommendations from DJKI and then given to Dit PAI Kominfo and will be continued to Telegram with the legal basis of the Joint Regulation of the Minister of Law and Human Rights and the Minister of Communication and Information Number 14 of 2015 and Number 26 of 2015 concerning the Implementation of Closing Content and / or Access Rights of Users of Copyright Infringement and / or Related Rights in Electronic Systems. Legal settlement in cases of copyright infringement of cinematographic films disseminated through the Telegram application during the Covid-19 pandemic through the district court for violating Law Number 28 of 2014 concerning Copyright Article 9 paragraph (1) letter a, letter b, letter e, and / or letter g Jo Article 113 paragraph (3) Jo Article 55 paragraph (1) of the Criminal Code.  ABSTRAK Masyarakat selama masa Covid-19 beralih dalam menonton film dari bioskop menjadi digital dengan membayar biaya layanan aplikasi, namun tidak semua masyarakat ingin membayar sejumlah biaya untuk menonton dan beralih menonton film melalui aplikasi Telegram, film dalam Aplikasi Telegram adalah film hasil pembajakan. Tujuan penelitian adalah: untuk menganalisis perlindungan hak cipta sinematografi film yang disebarluaskan melalui aplikasi Telegram selama masa pandemic Covid-19 dan untuk menjelaskan, penyelesaian hukum dalam kasus pelanggaran Hak Cipta sinematografi film yang disebarluaskan melalui aplikasi Telegram selama masa pandemic Covid-19. Metode penelitian yang digunakan adalah metode Normatif-Empiris. Sumber data yang digunakan adalah sumber data sekunder sumber data primer. Teknik pengumpulan data studi kepustakaan dan wawancara.  Analisis data yang digunakan analisis data kualitatif. Hasil dari penelitian ini bahwa, perlindungan hukum sinematografi film yang disebarluaskan melalui aplikasi Telegram selama masa pandemic Covid-19 yaitu melalui penutupan akun atau konten berdasarkan rekomendasi dari DJKI lalu diberikan ke Dit PAI Kominfo dan akan dilanjutkan ke Telegram dengan dasar hukum Peraturan Bersama Menkumham dan Menteri Komunikasi dan Informatika Nomor 14 Tahun 2015 dan Nomor 26 Tahun 2015 Tentang Pelaksanaan Penutupan Konten dan/atau Hak Akses Pengguna Pelanggaran Hak Cipta dan/atau Hak terkait dalam Sistem Elektronik. Penyelesaian hukum dalam kasus pelanggaran Hak Cipta sinematografi film yang disebarluaskan melalui aplikasi Telegram selama masa pandemi Covid-19 melalui pengadilan negeri karena melanggar Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta Pasal 9 ayat (1) huruf a, huruf b, huruf e, dan/atau huruf g Jo pasal 113 ayat (3) Jo Pasal 55 ayat (1) KUHPidana.